AKUISISI DATA 6 DEGREE OF FREEDOM DAN KOORDINAT MENGGUNAKAN SENSOR IMU, GPS, KOMUNIKASI LORA BERBASIS LABVIEW - Cahya, Delila; Setiawan, Budhy; Dewatama, Denda; Ali Akbar Febritama, Muhammad (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2024)
This research developed a data acquisition system for 6 Degrees of Freedom (6 DoF) and coordinates using an Inertial Measurement Unit (IMU) and Global Positioning System (GPS), with Long Range (LoRa) communication for data transmission. The system is integrated with LabVIEW for real-time data processing and visualization.The test results showed that the system is capable of accurately acquiring, transmitting, and displaying roll, pitch, yaw, and GPS coordinate data. The 3D model in LabVIEW represents the object's orientation and position in real-time, supporting various applications that require high-precision monitoring. LoRa successfully transmitted data over long distances without loss of integrity.This system provides a flexible solution for various industrial and research applications that require precise position and orientation monitoring. The implementation of this technology can support developments in autonomous navigation, surveillance systems, and robotics.